Gnostic Revisions of Genesis Stories and Early Jesus Traditions - Luttikhuizen, Gerard P., (Nag Hammadi and Manichaean Studies ;, 2006)
This book argues that the intellectuals behind early Gnostic revisions of Genesis stories were second-century Christians with an ideological background in Greek-Hellenistic philosophy, who adopted and reinterpreted biblical narrative materials with a view to exposing the inferiority of the creator-God of Genesis and the ignorance of those Christians who continued to worship this God. It also discusses controversies between Gnostic and early orthodox Christians about the person and the mission of Jesus Christ. The first part examines the possible polemical function, the philosophical thought structure, and the narrative scheme of the Genesis rewritings, and continues with studies of individual episodes of the Gnostic myth, from the creation of Adam up to the story of Noah and the Flood. The second part focuses on Gnostic reinterpretations of the teaching and the passion of Jesus. The book includes essays about Gnostic theology, ancient and modern readings of Gnostic texts, and an appendix dealing with the ancient baptist community in which Mani was reared.